AN1284 attenuates steatosis, lipogenesis, and fibrosis in mice with pre-existing non-alcoholic steatohepatitis and directly affects aryl hydrocarbon receptor in a hepatic cell line - Yehezkel, Adi S.; Abudi, Nathalie; Nevo, Yuval; Benyamini, Hadar; Elgavish, Sharona; Weinstock, Marta; Abramovitch, Rinat (Frontiers in Endocrinology, 2023)
Non-alcoholic steatohepatitis (NASH) is an aggressive form of fatty liver disease with hepatic inflammation and fibrosis for which there is currently no drug treatment. This study determined whether an indoline derivative, AN1284, which significantly reduced damage in a model of acute liver disease, can reverse steatosis and fibrosis in mice with pre-existing NASH and explore its mechanism of action. The mouse model of dietary induced NASH reproduces most of the liver pathology seen in human subjects. This was confirmed by RNA-sequencing analysis. The Western diet, given for four months, caused steatosis, inflammation and liver fibrosis. AN1284 (1 mg or 5 mg/kg/day) was administered for the last two months of the diet by micro-osmotic-pumps (mps). Both doses significantly decreased hepatic damage, liver weight, hepatic fat content, triglyceride, serum alanine transaminase and fibrosis. AN1284 (1 mg/kg/day) given by mps or in the drinking fluid significantly reduced fibrosis produced by carbon tetrachloride injections. In human HUH7 hepatoma cells incubated with palmitic acid, AN1284 (2.1 and 6.3 ng/mL), concentrations compatible with those in the liver of mice treated with AN1284, decreased lipid formation by causing nuclear translocation of the aryl hydrocarbon receptor (AhR). AN1284 downregulated Fatty acid synthase (FASN) and sterol regulatory element-binding protein 1c (SREBP-1c) and up-regulated Acyl-CoA Oxidase 1 and Cytochrome P450-a1, genes involved in lipid metabolism. Conclusion: Chronic treatment with AN1284 (1 mg/kg/day) reduced pre-existing steatosis and fibrosis through AhR, which affects several contributors to the development of fatty liver disease. Additional pathways are also influenced by AN1284 treatment.